EFFECTIVENESS OF BREAST CRAWL BY MIDWIVES TO INCREASE BREAST MILK PRODUCTION AMONG POSTPARTUM MOTHERS - Sarita, Sultina; Syahrianti, Syahrianti; P, Nurnasari (YCAB Publisher & IAKMI SULTRA, 2020)
Background: Normal Childbirth Care or APN is a standard or a reference for childbirth assistance and a breast crawl, or called IMD, in Indonesia; however, there is lack of its implementation in the midwifery practice. Breast crawl is considered effective in increasing breast milk production among postpartum mothers.Objective: The aim of the study was to determine the effectiveness of breast crawl by midwives to increase the breast milk production in postpartum mothers in Kendari, Indonesia.Methods: True experimental study with posttest only control group design. A total of 30 midwives participated using a total sampling technique. Respondents were given intervention regarding the implementation of breast crawl using the breast crawl pocket book as a research instrument. Data were analyzed using Mann-Whitney test to determine the differences in respondents who were given IMD intervention using the breast crawl pocket book and the control group who did not use the breast crawl pocket book.Result: There was a significant difference between respondents who were given intervention using pocket books and the control group who did not use pocket books with p = 0.039 (<0.05).Conclusion: There was a significant difference between the breast milk production of postpartum mothers who were given breast crawl intervention and those who were not given breast crawl intervention by midwives. This intervention is therefore recommended as one of midwifery cares in the community health centers.